Effectivity of guided discovery learning supported with elemental chemistry e-module on students learning outcomes - Elga Joninda Putri; Yerimadesi Yerimadesi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to analyze the effectiveness of the elemental chemistry e-module based on guided discovery learning in improving student learning outcomes. The research was conducted in class XII at a public high school (SMAN 13 Padang) with 36 students. The type of research used is quasi-experimental. Research design is a one-group pretest-posttest design and data analysis using a t-test. Sampling using a simple random sampling technique. The level of effectiveness of the e-module was analyzed from the results of the n-gain value. The obtained n-gain value is 0.49 in the medium category. In conclusion, the guided discovery learning-based e-chemistry module effectively improves student learning outcomes with high criteria.